The injection capacity evaluation of high-pressure water injection in low permeability reservoir: numerical and case study - Zhu, Weiyao; Gao, Yubao; Wang, Youqi; Liu, Ping; Liu, Yunfeng (Frontiers in Earth Science, 2024)
Low permeability oil reservoir resources are rich and their efficient development is considered an important way to solve energy security issues. However, the development process of low permeability oil reservoirs is faced with the challenges of insufficient natural energy and rapid production decline.The high-pressure water injection technology is a method that relies on high-pressure and large-volume to inject fluid into the reservoir to replenish energy. It is considered as an important technical means to quickly replenish formation energy. This study focuses on the injection capacity for the highpressure water injection technology of low permeability oil reservoir. Firstly, the fluid-structure interaction mathematical model for two-phase fluid flow was established. The solution of the mathematical model was then obtained by coupling the phase transport in porous media module and Darcy's law module on the COMSOL numerical simulation platform. The numerical model established in this study was verified through the Buckley-Leverett model. The study on the injection capacity of high-pressure water injection technology was conducted using the geological background and reservoir physical properties of Binnan Oilfield (Shengli, China). The results show that the production pressure difference is the key factor in determining the injection capacity. When the production pressure difference increases from 5MPa to 30MPa, the cumulative injection volume increases by 8.1 times. In addition, sensitivity analysis shows that the injection capacity is significantly influenced by the properties of the reformation area. The effect of these parameters from high to low is as follows: stress sensitivity factor, permeability, rock compressibility, and porosity. Compared to the reformation area, the influence of the physical parameters of the matrix area on the injection capacity is negligible. Therefore, effective reservoir reformation is essential for enhancing the injection capacity. This research provides a theoretical basis for the design and optimization of the high-pressure water injection technology schemes for low permeability oil reservoir.